2013
DOI: 10.1089/scd.2013.0089
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Cell Therapy Trials for Stroke: Review of Published and Registered Studies

Abstract: Stroke is the second leading cause of death and the third leading cause of disability worldwide. Approximately 16 million first-ever strokes occur each year, leading to nearly 6 million deaths. Nevertheless, currently, very few therapeutic options are available. Cell therapies have been applied successfully in different hematological diseases, and are currently being investigated for treating ischemic heart disease, with promising results. Recent preclinical studies have indicated that cell therapies may provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 136 publications
0
39
0
Order By: Relevance
“…Stroke in particular has been assessed by many groups as a potential target for cell replacement, and was among the first targets of stem and progenitor cell-based transplantation. (Hara et al, 2008; Nelson et al, 2002; Rosado-de-Castro et al, 2013). Yet stroke occurs in a fundamentally compromised environment of ischemic infarct, often in regions that have suffered chronic hypoxic ischemia, with its attendant gliosis and inflammation.…”
Section: Hype: Limits To Therapeutic Advancementioning
confidence: 99%
“…Stroke in particular has been assessed by many groups as a potential target for cell replacement, and was among the first targets of stem and progenitor cell-based transplantation. (Hara et al, 2008; Nelson et al, 2002; Rosado-de-Castro et al, 2013). Yet stroke occurs in a fundamentally compromised environment of ischemic infarct, often in regions that have suffered chronic hypoxic ischemia, with its attendant gliosis and inflammation.…”
Section: Hype: Limits To Therapeutic Advancementioning
confidence: 99%
“…Multiple types of stem cells such as neural stem cells (NSCs) and MSCs have so far shown potent immunomodulatory and neuroprotective properties in the models of human ischemic and hemorrhagic stroke[14, 29, 30, 3436]. For example, Lee et al [5] reported that intravenously injected NSCs have neuroprotective and anti-inflammatory actions in hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…80 Although stem cells are neuroregenerative, rather than neuroprotective, their intraarterial delivery is worth considering in this discussion. At this time, the optimal mode of stem cell delivery (intracerebral, intraventricular, subarachnoid, intraarterial, intraperitoneal, intravenous, and intranasal) remains unclear.…”
Section: Intraarterial Neuroprotectant Deliverymentioning
confidence: 99%